2017
DOI: 10.7150/thno.18990
|View full text |Cite
|
Sign up to set email alerts
|

MiR-205/YAP1 in Activated Fibroblasts of Breast Tumor Promotes VEGF-independent Angiogenesis through STAT3 Signaling

Abstract: Tumor microenvironment contributes to tumor angiogenesis. However, the role of the activated cancer associated-fibroblasts (CAFs) in angiogenesis is still unclear. Here we report that miR-205/YAP1 signaling in the activated stromal fibroblasts plays a critical role in VEGF-independent angiogenesis in breast tumor. Methods: miR-205 expression was assessed by quantitative real-time polymerase chain reaction (qRT-PCR); YAP1 expression by qRT-PCR, western blotting and immunohistochemistry; IL11 and IL15 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 54 publications
3
68
0
Order By: Relevance
“…Donnarumma et al found that breast cancer cells cultured by the CAFs‐derived exosomes exhibited a significantly increased ability to form mammospheres, anchorage‐independent cell growth and higher expression of stem cell and EMT markers . It is also reported that, in breast cancer, the activated stromal fibroblasts could contribute to the VEGF‐independent angiogenesis via the miR‐205/YAP1 signaling . In HCC, Liu et al showed that CAFs promote HCC metastasis through the activation of Hedgehog and TGF‐β pathways via chemokines .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donnarumma et al found that breast cancer cells cultured by the CAFs‐derived exosomes exhibited a significantly increased ability to form mammospheres, anchorage‐independent cell growth and higher expression of stem cell and EMT markers . It is also reported that, in breast cancer, the activated stromal fibroblasts could contribute to the VEGF‐independent angiogenesis via the miR‐205/YAP1 signaling . In HCC, Liu et al showed that CAFs promote HCC metastasis through the activation of Hedgehog and TGF‐β pathways via chemokines .…”
Section: Discussionmentioning
confidence: 99%
“…37 It is also reported that, in breast cancer, the activated stromal fibroblasts could contribute to the VEGF-independent angiogenesis via the miR-205/YAP1 signaling. 38 In HCC, Liu et al showed that CAFs promote HCC metastasis through the activation of Hedgehog and TGF-β pathways via chemokines. 9 Collectively, these results revealed that CAFs-tumor cell crosstalk facilitates the progression of tumors.…”
Section: Te-1mentioning
confidence: 99%
“…Moreover, STAT3 modulates the expression of genes involved in anti-apoptosis (Bcl-2, Bcl-xL, and survivin), proliferation (cyclin D1) [11], and angiogenesis (VEGF) [12]. Recently, studies have reported that STAT3 is constitutively activated in many cancers, including breast cancer [13], ovarian cancer [14], and lung cancer [15]. Inhibition of STAT3 cascade-related protein expression has been shown to induce cell cycle arrest and apoptosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…miR-200s target friend leukemia virus integration 1 (Fli-1) and transcription factor 12 (TCF12) in the breast cancer microenvironment (32,33). Moreover, decreased miR-205 was shown to convert breast NFs into CAFs by promoting Yes-associated protein 1 (YAP1) expression, which has been proven to be involved in angiogenesis (34).…”
Section: Role Of Micrornas In Remodeling the Tumor Microenvironment (mentioning
confidence: 99%
“…In breast cancer, tumor cells can release miR-939 to endothelial cells via exosomes, and miR-939 was shown to suppress the expression of its target gene vascular endothelial-cadherin in endothelial cells, increasing vascular permeability (66). Moreover, miR-205 suppression in other cells of the TME, including CAFs, was reported to enhance tubule formation and sprouting of endothelial cells by regulating YAP1-mediated IL-11 and IL-15 expression and secretion (34). In prostate cancer, miR-218 downregulation was shown to promote tumor angiogenesis through the regulatory-associated protein-independent companion of mammalian target of rapamycin complex 2/VEGFA axis (67).…”
Section: Role Of Mirnas In Regulating Tumor-associated Macrophagesmentioning
confidence: 99%